Need for Human Rights Education for Female Children: A Case Study in Tuticorin District, Tamil Nadu - Amutha, D. (Prabandhan: Indian Journal of Management, 2011)
Education is a fundamental human right as well as a catalyst for economic growth and human development. Women’s education is extremely important intrinsically as it is their human right and is required for the flourishing of many of their capacities. The present study has been conducted with an objective to have in-depth insight into the problem of female school dropouts in primary to higher secondary classes in Tuticorin District of Tamil Nadu.